New records of four-lined snake (Elaphe quatuorlineata) in Natura 2000 site Slovenska Istra (SI3000212) - Vesna Cafuta (Natura Sloveniae)
The article presents new records of ten specimens (one juvenile, one subadult and eight snake sheddings) of four-lined snake (Elaphe quatuorlineata) recorded in a period between May 2002 and March 2011 on seven locations in Natura 2000 site Slovenska Istra (SI3000212). In some locations, the species was observed several times. Data show successful reproduction within the abovementioned Natura 2000 site.